2011 IEEE 11th International Conference on Data Mining Workshops 2011
DOI: 10.1109/icdmw.2011.97
|View full text |Cite
|
Sign up to set email alerts
|

Imputation of Missing Links and Attributes in Longitudinal Social Surveys

Abstract: Abstract-We propose a unified approach for imputation of the links and attributes in longitudinal social surveys which accounts for changing network topology and interdependence between the actor's links and attributes. The previous studies on the treatment of non-respondents in longitudinal social networks were mostly concerned with imputation of the missing links only or imputation effects on the networks statistics. For this study we conduct a set of experiments on synthetic and real life datasets with 20%-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Model-based methods for missing cross-sectional network data were proposed by Robins et al (2004), Handcock and Giles (2010), Koskinen et al (2010Koskinen et al ( , 2013, all within the family of exponential random graph models. Imputation methods for crosssectional network data were proposed and examined by Huisman (2009), Wang et al (2016), Huisman and Krause (2017), and Krause et al (2018b), and for missing longitudinal network data by Huisman and Steglich (2008), Ouzienko and Obradovic (2014), Hipp et al (2015), and Krause et al (2018a). A combination of available case strategies and imputation within SAOMs (i.e., the default method implemented in the SIENA software) was examined by Hipp et al (2015), de la Haye et al (2017), and Krause et al (2018a).…”
Section: Treatments For Missing Behavior Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Model-based methods for missing cross-sectional network data were proposed by Robins et al (2004), Handcock and Giles (2010), Koskinen et al (2010Koskinen et al ( , 2013, all within the family of exponential random graph models. Imputation methods for crosssectional network data were proposed and examined by Huisman (2009), Wang et al (2016), Huisman and Krause (2017), and Krause et al (2018b), and for missing longitudinal network data by Huisman and Steglich (2008), Ouzienko and Obradovic (2014), Hipp et al (2015), and Krause et al (2018a). A combination of available case strategies and imputation within SAOMs (i.e., the default method implemented in the SIENA software) was examined by Hipp et al (2015), de la Haye et al (2017), and Krause et al (2018a).…”
Section: Treatments For Missing Behavior Datamentioning
confidence: 99%
“…Imputation methods for behavior data are scarcely investigated. Ouzienko and Obradovic (2014) present an ERGM-based imputation model for imputing both missing tie variables and missing actor behaviors for longitudinal network data. For missing behavior variable in SAOMs, Ripley et al (2017) propose a simple imputation scheme in which either the previous observation, the next observation, or the mode of the variable is imputed, in order of availability.…”
Section: Treatments For Missing Behavior Datamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the standard ways of handling missing values is imputing values based on some predictive model, and then applying the analysis on a fully observed dataset. To exploit the graph structure, previous studies have proposed imputation of missing values based on the exponential random graph model [15]. The limitation of such an approach is that it is slow, as it requires Gibbs sampling, and so it cannot handle large graphs.…”
Section: Related Workmentioning
confidence: 99%
“…Koskinen et al (2013) illustrate the effect of missing behavior data and present an ERGM-based procedure to analyze the incomplete data. Ouzienko and Obradovic (2014) propose an ERGM-based imputation procedure for the case of longitudinal network data (i.e., temporal ERGMs). In a small simulation study, using simulated and reallife data, they showed that, in general, their imputations result in more accuracy in predicting tie and behavior variables (comparing observed and imputed scores) than simpler methods.…”
mentioning
confidence: 99%